2022
DOI: 10.1101/2022.04.05.22273075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent racial disparities in deep brain stimulation for Parkinson’s disease

Abstract: We sought to determine whether racial and socio-economic disparities in the utilization of deep brain stimulation (DBS) for Parkinson’s disease (PD) have improved over time. We examined DBS utilization and analyzed factors associated with placement of DBS. The odds of DBS placement increased across the study period while White PD patients were 5 times more likely than Black patients to undergo DBS. Individuals, regardless of racial background, with two or more comorbidities were 14 times less likely to undergo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Our current review found a gender disparity (Hariz and Hariz, 2000;Setiawan et al, 2006;Willis et al, 2014;Shpiner et al, 2019;Cramer et al, 2022;Deshpande et al, 2022;Jost et al, 2022;Watanabe et al, 2022) and suggested that the proportion of male patients undergoing STN DBS appears to exceed the reported 1.48: 1 male-tofemale ratio among patients with PD (Katz et al, 2011;Moisan et al, 2016;Shpiner et al, 2019). Three research studies sought to elucidate the factors underlying the observed gender disparity.…”
Section: Gender Disparitymentioning
confidence: 73%
See 4 more Smart Citations
“…Our current review found a gender disparity (Hariz and Hariz, 2000;Setiawan et al, 2006;Willis et al, 2014;Shpiner et al, 2019;Cramer et al, 2022;Deshpande et al, 2022;Jost et al, 2022;Watanabe et al, 2022) and suggested that the proportion of male patients undergoing STN DBS appears to exceed the reported 1.48: 1 male-tofemale ratio among patients with PD (Katz et al, 2011;Moisan et al, 2016;Shpiner et al, 2019). Three research studies sought to elucidate the factors underlying the observed gender disparity.…”
Section: Gender Disparitymentioning
confidence: 73%
“…Our review revealed that the availability of DBS among Black individuals is lower (Chan et al, 2014;Willis et al, 2014;Cramer et al, 2022;Dorritie et al, 2023;Skelton et al, 2023). Table 2 provides details of the included studies.…”
Section: Racial Disparitymentioning
confidence: 92%
See 3 more Smart Citations